Study on Innovative Behavior of “X” Hotel Employees In Surabaya - Tri Siwi Agustina; Fadlilah Karunia Novianti (Journal Research of Social Science, Economics, and Management, 2021)
Uncertainty is always faced in an ever-changing business environment, this makes organizations must have the readiness and ability to create innovations. This study aims to analyze the effect of perceived peer support and perceived organizational support on innovative behavior. This study uses work engagement as a mediating variable, and leader-member exchange as a moderating variable. This research was conducted at Hotel X Surabaya, which is part of a four-star national hotel chain. The sample used is the operational employees of Hotel X Surabaya, which means 40 employees. Next, the trial uses the least-squares portion (PLS). The results of this study indicate that work engagement fully mediates the relationship between perceived peer support and innovative behavior. This shows that the perception of peer support does not directly affect innovative behavior. Furthermore, on the relationship between perceived organizational support and innovative behavior, the job involvement variable partially mediates. This study also shows the results that leader-member exchange strengthens the relationship between perceived organizational support and innovative behavior. Thus, for high-level leader-exchange members, the relationship between perceived organizational support and innovative behavior was stronger than for low-leader-member exchanges.